(untitled) (TEST Ticontre. Theory Text Translation, 2025)
How can memory be preserved when historical evidence is no longer there? Is it really possible to reconstruct a multi-layered history starting from a few remains left by a culture in danger of extinction? Do the red stones displayed in a souvenir shop really have “memory and power,” as Native American poet Joy Harjo believes in “New Orleans”? By analyzing a selection of poems included in the collection Weaving Sundown in a Scarlet Light: 50 Poems for 50 Years (2023), the essay explores the relation between individual memory, tribal stories, and contemporary challenges. In traditional oral cultures, such as the Native American one, it is the art of telling stories that has the noble task of recovering, passing on, and preserving memory. In order to combat the cultural amnesia resulting from the annihilation and cultural alienation induced by colonialism and aggressive assimilative practices, it is towards the earth that one must turn. By listening to the stories contained in it, by amplifying them, and by passing them down to the next generation, Harjo recovers a memory buried in the bowels of the earth for millennia, while also interrupting and complementing official colonial historiography with alternative truths. With the earth as its focus, in this essay I will explore the role played by individual and collective memory in Harjo’s poetry and more in general in contemporary Native American poetry. Come preservare la memoria quando le evidenze storiche non ci sono più? È possibile ricostruire una storia stratificata a partire da pochi resti lasciati da una cultura in via d’estinzione? Davvero le pietre rosse esposte in un negozio di souvenir sono dotate di «memoria e potere», come afferma la poeta nativo-americana Joy Harjo in "New Orleans”? Attraverso l’analisi di poesie selezionate dalla raccolta Weaving Sundown in a Scarlet Light: 50 Poems for 50 Years (2023), il saggio interroga il rapporto tra memoria individuale, storie ancestrali e sfide contemporanee. Nelle culture orali tradizionali, come quella nativo-americana, è l’arte del raccontare storie che ha il nobile compito di recuperare, tramandare e preservare la memoria. Per combattere l’amnesia, frutto dell’annientamento e dell’alienazione culturale indotti dal colonialismo e da pratiche assimilative aggressive, non resta che mettersi in ascolto della terra, amplificare le storie in essa contenute e ritrasmetterle di generazione in generazione. Tali storie hanno un’importanza fondamentale per Harjo, non solo perché recuperano dalle viscere della terra una memoria sepolta da millenni, ma anche perché arricchiscono la storia ufficiale con un controcanto capace di interrompere la storia coloniale. Sarà dunque a partire dalla terra che in questo saggio si esplorerà il ruolo della memoria nella poesia di Harjo e più in generale nella poesia nativo-americana contemporanea.